Perlindungan Hukum Terhadap Konsumen Dalam Transaksi Online E-commerce: Studi Atas Undang-Undang Nomor 8 Tahun 1999 Tentang Perlindungan Konsumen Pasal 18 - Fikri, Moh. Lazim; Nurfransiska, Ferika; Lutfianidha, Redyana (Universitas Muhammadiyah Kotabumi, 2025)
Abstrak : Consumer protection in transactions on e-commerce platforms is a very important issue in legal certainty for consumers. The purpose of this study is to formulate the role of consumer protection regulations and efforts to resolve e-commerce transaction disputes. The normative approach is carried out by analyzing Law Number 8 of 1999 Article 18 and other regulations. Meanwhile, the empirical approach is to conduct a field survey with data analysis using the PLS-SEM method. The measurement results showed valid and reliable research indicators. Meanwhile, the results of testing on structural equations show the important role of consumer protection and dispute resolution on the level of consumer satisfaction. In addition, consumer satisfaction also plays a role in consumer loyalty in online e-commerce transactions